The limits of sportswashing. How the 2022 FIFA World Cup affected attitudes about Qatar - Johannes Gerschewski; Heiko Giebler; Sebastian Hellmeier; Eda Keremoğlu; Michael Zürn (PLOS ONE, 2024)
Non-democratic regimes have increasingly been hosting major sports events to boost their visibility and image abroad, which sparked debates about the potential for “sportswashing”. Using the case of the 2022 FIFA World Cup in Qatar we examine how the framing of the tournament influenced opinions about Qatar abroad. Our pre-registered survey experiment with more than 14,000 respondents in eight European countries conducted before the tournament shows that framing it in light of human rights issues in Qatar leads to more negative attitudes towards the host of the World Cup. In contrast, frames emphasizing Qatar's organizational capacity improve respondents' attitudes. The heterogeneity of effects across countries highlights the relevance of the national information environment for the effects of major sports events on public opinion. These findings suggest that critical media coverage could potentially mitigate sportswashing efforts while uncritical coverage can increase the legitimacy of autocracies.
https://doi.org/10.7910/DVN/PKIPXM
Keywords: 300